Translating National Energy Vision into Local Scenarios - Bang, Aksel; Nielsen, Steffen; Lund, Henrik (International Journal of Sustainable Energy Planning and Management, 2025)
The energy transition toward a fully decarbonized society requires meaningful actions on a global scale, implemented at the local level. This requires translating a global perspective into local energy planning to implement actions that envisage the local energy system in a broader context. This article aims to translate a fully decarbonized national future scenario shaped by a global perspective to the local level of a Danish municipality. To create an accurate translation of a national scenario, analyzing local potential and constraints is crucial to understand how a specific municipality can become an integral part of a national scenario. To do this, the article outlines four methodological steps for translating and exploring an overarching national scenario in a local context. The article illustrates how a national energy system scenario can inform local energy planning as part of a coherent national energy transition. The article indicates that local energy planning in Denmark can also benefit from this translation to comprehend the national energy transition at the local level, by seeing the local energy planning as part of a more integrated future national decarbonized society.